Evaluasi Kristis Pandangan Teologi Kemakmuran Tentang Pemahaman Makna Penderitaan - Waruwu, Elifati; Sapan, Naomi (CARAKA: Jurnal Teologi Biblika dan Praktika, 2024)
Prosperity theology is a movement that emerged and became a phenomenon in itself that has greatly influenced Christian life since the 20th century. For prosperity theology, suffering is a sin and is not pleasing to God for those who experience suffering. So, when prosperity theology talks about the suffering that occurs in the lives of believers, this teaching sees it as God's curse, prosperity theology believes that believers must be materially rich, physically healthy and have an abundant life. The doctrine of prosperity theology is too attractive and rejects the suffering that occurs in the lives of believers. The presence of prosperity theology teachings raises problems related to Christian theology. This paper uses qualitative methods through a systematic theology approach. This approach is taken to see how prosperity theology builds its theology, and evaluates it. Prosperity theology builds its theology based on John 10:10b and interprets it with its own understanding without paying attention to the actual meaning. The conclusion of this scientific work is to provide correct understanding for believers and also to correct incorrect understanding of prosperity theology.